Analisis Daya dan Performa Sistem Pengamanan Kendaraan Berbasis Internet of Things - Mochamad Sidqon; Agung Kridoyono; Elvianto Dwi Hartono; Anton Breva Yunanda (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2025)
A power analysis and performance study of a vehicle safety system combines vehicle contactor control, battery voltage monitoring, and an automatic disconnect feature to maintain power stability. Quantitative system performance measurements using statistical and probability approaches included connection reliability, voltage drop patterns, current distribution, and the relationship between operating time and power consumption. A total of 300 observation data sets were collected from a controlled testing process. The results show that battery voltage drop follows a negative linear trend with a correlation coefficient of -0.54, indicating a moderate relationship between load duration and voltage degradation. Analysis of relay response probabilities and WiFi connectivity showed a 96.3% success rate and a 3.7% probability of connection failure under standard network conditions. The distribution of errors in voltage measurements tended to follow a log-normal pattern based on the Kolmogorov–Smirnov test. The findings confirm that the safety control system performs stably in most test scenarios, but requires specific optimization when peak currents occur